Draft Annual Plan 1976-77 Volume V (Transport and Communications) Roads, Transport and Tourism Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1976)
In order to ensure early completion of spillover schemes adequate funds have been allocated. The financial allocation being United, the schemes under Minimum Needs Programme of New Schemes could net be provided with adequate provision. The cost of Tar, Cement etc. has increased considerably which is also responsible for the limited allocation for new schemes and Minimum Need Programme Schemes.
Government of Jammu and Kashmir, Department of Planning and Development